2022
DOI: 10.1002/cctc.202200293
|View full text |Cite
|
Sign up to set email alerts
|

An Intermetallic CaFe6Ge6 Approach to Unprecedented Ca−Fe−O Electrocatalyst for Efficient Alkaline Oxygen Evolution Reaction

Abstract: Based on the low-cost and relatively high catalytic activity, considerable efforts have been devoted towards developing redox-active transition metal (TM)-oxygen electrocatalysts for the alkaline oxygen evolution reaction (OER) while the role of redox-inactive alkaline earth metals has often been neglected in OER. Herein, for the first time, we developed a novel ternary intermetallic CaFe 6 Ge 6 precatalyst, whose surface rapidly transforms into a porous ultrathin CaÀ FeÀ O heteroshell structure during alkalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 72 publications
(171 reference statements)
0
17
0
Order By: Relevance
“…The nature of in situ -formed species is mainly dominated by the structure of the pristine materials and the thermodynamic stability of anions as well as by the test conditions. Intermetallic compounds have emerged as a new class of OER electrocatalysts, as they showed ordered structures and a peculiar bonding properties. ,, Compared to unordered alloys, intermetallic compounds excel through high thermodynamic stability, so that employment of intermetallic compounds for the OER can be promising. ,, However, some of the reported intermetallic electrocatalysts also showed partial or complete structural transformation under harsh OER conditions. For example, using in situ Raman spectroscopy, Shen et al revealed the presence of a NiOOH layer on the surface of MoNi 4 during the OER .…”
Section: Mechanistic Insights Into Oer Catalysts Via In Situ/operando...mentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of in situ -formed species is mainly dominated by the structure of the pristine materials and the thermodynamic stability of anions as well as by the test conditions. Intermetallic compounds have emerged as a new class of OER electrocatalysts, as they showed ordered structures and a peculiar bonding properties. ,, Compared to unordered alloys, intermetallic compounds excel through high thermodynamic stability, so that employment of intermetallic compounds for the OER can be promising. ,, However, some of the reported intermetallic electrocatalysts also showed partial or complete structural transformation under harsh OER conditions. For example, using in situ Raman spectroscopy, Shen et al revealed the presence of a NiOOH layer on the surface of MoNi 4 during the OER .…”
Section: Mechanistic Insights Into Oer Catalysts Via In Situ/operando...mentioning
confidence: 99%
“…Meanwhile, the in situ -formed γ-NiOOH contained a large interplanar spacing that enabled the ionic intercalation of OH – /CO 3 2– , thus improving the ECSA and electronic conductivity to promote the OER. On the other hand, using the same molecular-complex-derived route, intermetallic Fe 6 Ge 5 and CaFe 6 Ge 6 catalysts were prepared for the OER, and the results showed that both intermetallics were found to rearrange into a core–shell structure that contained a porous FeOOH shell and the pristine intermetallic core. The observed high OER activities were explained by the increased surface areas with rich Fe site exposure accompanied by Ge leaching.…”
Section: Mechanistic Insights Into Oer Catalysts Via In Situ/operando...mentioning
confidence: 99%
“…For further development of the field, more in‐situ characterization methods must be exploited such as X‐ray absorption spectroscopy on the anion edges, which could finally provide geometrical information on the bonding situation of the (oxy)anion. Furthermore, besides anions, also cations can surface‐adsorb or intercalate into the interlayer space and thus might have similar effects on the OER [97, 98] . This is particularly important as every anion comes with a cation, and to date, it is unclear if the addition of, e.g., sodium sulfate has the same effect as potassium or magnesium sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, besides anions, also cations can surface-adsorb or intercalate into the interlayer space and thus might have similar effects on the OER. [97,98] This is particularly important as every anion comes with a cation, and to date, it is unclear if the addition of, e.g., sodium sulfate has the same effect as potassium or magnesium sulfate. We anticipate that this critical Minireview will provide guidance for the analysis of these phenomena and will motivate and help researchers to participate in this novel and exciting OER research direction.…”
Section: Discussionmentioning
confidence: 99%
“…To date, state-of-the-art catalysts RuO x and IrO x are known to showcase the best performance for oxygen evolution reaction (OER) and Pt for hydrogen evolution reaction (HER). [11,12] Considering the price and the non-abundant nature of these metals, intense efforts have been put into designing cost-effective electrocatalysts based on transition-metal (TM) oxides/ hydroxides/(oxy)hydroxides, [13][14][15][16][17] chalcogenides, [18][19][20] pnictides, [21] phosphides, [22] borides, [23,24] borophosphates, [25,26] carbides, [27] alloys, [28] intermetallics, [29][30][31][32] and their heterostructures; as well as ligand-assisted metal-organic frameworks (MOFs), [33][34][35] covalent organic frameworks (COFs), [36,37] and metal oxalates [38,39] for both OER [40,41] and HER [42] reactions. Most of these electrocatalysts show promising results in comparison to the benchmark noble-metal-based state-of-the-art catalysts.…”
Section: Introductionmentioning
confidence: 99%